The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1978
DOI: 10.2136/sssaj1978.03615995004200060020x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Substitution of Mycorrhizal Fungi for Phosphorus Fertilization in the Greenhouse Culture of Citrus

Abstract: The interaction between P fertilization of citrus and the mycorrhizal fungus Glomus fasciculatus was examined in a greenhouse study. A low fertility loamy sand (4.6 ppm P) was provided with all necessary soil nutrients except P. This soil received superphosphate [Ca(H2PO4)2 · H2O] at rates of 0, 6, 28, 56, 278, and 556 ppm of P. Seven replicate mycorrhizal and nonmycorrhizal Brazilian sour orange and Troyer citrange seedlings were grown at each P fertility level. After 5 months, mycorrhizal sour orange which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 0 publications
5
32
0
1
Order By: Relevance
“…Increasing levels of soluble P fertiliser generally depress mycorrhizal infection levels in plant roots (Baylis 1967;Mosse 1973;Menge et al 1978), butthe experimental results discussed in this paper confirm earlier reports that mycorrhizal infection levels are usually unaffected by high levels of rock phosphate (Daft & Nicholson 1966;Powell 1977;Powell & Daniel 1978a) even when this fertiliser is effectively stimulating plant growth.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Increasing levels of soluble P fertiliser generally depress mycorrhizal infection levels in plant roots (Baylis 1967;Mosse 1973;Menge et al 1978), butthe experimental results discussed in this paper confirm earlier reports that mycorrhizal infection levels are usually unaffected by high levels of rock phosphate (Daft & Nicholson 1966;Powell 1977;Powell & Daniel 1978a) even when this fertiliser is effectively stimulating plant growth.…”
Section: Discussionsupporting
confidence: 90%
“…Growth responses to mycorrhizal inoculation should be compared with the growth responses possible from using phosphorus fertiliser alone (Abbott & Robson 19n;Hall 1978;Menge et al 1978). Powel1 (1980) showed that white clover in pot experiments responded to mycorrhizal inoculation in two highly P-retentive soils at superphosphate rates up to 1770 kg.ha -(.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that an increase in the available soil phosphorus due to the application of phosphorus fertilizers lowers the density of AM fungi spores in the soil. There have been many reports that the more phosphorus fertilizer applied, the lower the spore density (Menge et al, 1978;Isobe et al, 1993;Kahiluoto et al, 2001). In other words, to increase the density of AM fungi spores in soil, it is important to avoid excessive application of phosphorus fertilizers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is now clear that phosphorus is also important in the control of VA mycorrhizal infection of root systems (Mosse, 1972(Mosse, , 1973Sanders, 1975;Menge et al, 1977). However, the mechanism of phosphorus control of mycorrhizal symbiosis needs to be determined.…”
Section: Introductionmentioning
confidence: 99%